A Numerical Analytical Method of Parameter Optimization for Fast-starting of the Bionic Robot Fish - Yang, Chao (International Journal of Online and Biomedical Engineering (iJOE), 2013)
In this study,the alloy sheet, the giant magnetost- rictive material (GMM), was stuck on the sheet, and the external magnetic field were simulated as the framework of the fishtail, respectively; the muscle of the fish and the nerve are to control the swing of the fishtail for simulating the fast-starting of some natural fishes. Simulate the Fast-starting of fish different environment of nature. A mechanics model and new numerical method are presented by analyzing the vibrational modes. Optimization for External Parameter was conducted by using numerical computation, the best environment and material for Fast-starting of the Bionic Robot fish is revealed. Results show that the suit material can help the robot fish complete the fast-transition from the lower order mode to the higher order mode. The method and results provide theoretical foundation and applies basis to designing bionic robot fish.